Kinerja Instruktur Pendidikan Dan Pelatihan Keterampilan Pada Panti Sosial Bina Remaja Majar Tabela Kota Palangka Raya - Sonedi Sonedi; Lelisa Noviyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This research aims to find out, describe and analyze the performance of educational instructors and skills training at the youth community Development of Majar Tabela City Palangka Raya. While the research method used is qualitative. Researchers want to describe and analyze the performance of educational instructors and skill training at the Majar Tabela Youth Development Community in the six (6) Aspects of quality, quantity, timeliness, cost-effectiveness, need for supervision and Interpersonal impact. Data sources consist of primary data sources, which are interviews with 4 (four) instructors, 2 (two) Students/clients, and the head of Sub administration representing the head of Youth Development (PSBR) Majar Tabela, while the secondary data source is Official document of the Youth Development Community (PSBR) Majar Tabela. The results showed that the instructor's performance was still less than optimal. This can be seen from the quantity aspect is still a lack of instructors there are at least 6 (six) to 8 (eight) people, while the one is now only 4 (four) instructors. Then, from the need for supervision aspect, there are still less independent instructors, especially with regards to the creation of reports and learning evaluations. This is because the instructor is newly recruited so that it is still less experienced in making reports and evaluation activities. Thus causing the timeliness aspect is also impacted by delays in making activity reports. Therefore, the head of Youth Development Social Orphanage (PSBR) Majar Tabela City Palangka Raya is 1) increasing the number of instructors who are experienced in their field, both in the field of automotive and sewing, 2) provide technical guidance to the new instructor So that it can be independent (need for supervision) and timeliness in making final reports as well as evaluation of activities, and 3) reviewing the honor of the instructor to improve the instructor's commitment to improve the performance of instructors.